Pengembangan Desa Mandiri Sesuai Local Wisdom - Sujatmiko Aji; Syahrul Mursid; Yohanes Andika S. B; Yopi Santoso; Yulia Rahmawati; Yulinda Purbasari; Yusuf Rabbani; Yusuf Samsul A; Zakiudin Fahril A; Idam Ragil W. A (BALE LITERASI, 2022)
Kuliah Kerja Nyata (KKN) was held in Kertodeso Village, Mirit District, Kebumen Regency for 45 days starting on January 16, 2022 – March 2, 2022. The abundant potential of the village is one of the main objectives of implementing KKN to improve the quality of Human Resources (HR) in processing and developing the potential of the local village. Based on the results of the initial survey conducted through discussions with the apparatus and the village community, it is known that the problems that are considered to have an effect on the lives of the people of Kertodeso Village are related to economic and educational aspects. To solve these problems, the KKN 92 team UNS 2022 work program in Kertodeso Village which is in line with the sustainable development goals proclaimed by the government will focus on several points listed in the SDGs. Therefore, the main program objectives and the supporting programs compiled by the community can help develop the village's potential, and have a positive impact on the people of Kertodeso Village. To be able to achieve these goals, several activity plans are proposed in the implementation of the UNS 2022 Community Service Program in Kertodeso Village, as follows: Updating data, counseling on BumDes governance, processing patent formulations related to BumDesbusiness products, namely Soap and Honey, designing the polindes building, making village chronicles, community service activities with residents, making village information maps, village volleyball competitions, counseling on healthy living movements and class cleanliness competitions for elementary school students and making village profile videos. Based on the work programs carried out, students act as facilitators, dynamists and motivators. And every activity that has been taking place continuously is maintained to equip themselves as provisions in the future. Keywords: Kuliah Kerja Nyata, Kertodeso Village, BumDes, Socialization